Critical ranges of macronutrient leaf levels in coffee (Coffea arabica L.) after planting - first year - Clemente, Flávia Maria Vieira Teixeira; Carvalho, Janice Guedes de; Guimarães, Rubens José; Mendes, Antônio Nazareno Guimarães (Coffee Science - ISSN 1984-3909, 1970)
The critical ranges of leaf macronutrient levels coffee plants (Coffea arabica L.) in the first year after planting were determined in an experiment in greenhouse conditions in the Coffee Section at Universidade Federal de Lavras, in Lavras/MG. The experimental design used was randomized blocks with six treatments (levels of fertilization): 25, 50, 75, 100, 125 and 150% of standard fertilization, with four replicates and the evaluations were made in six different times: 30, 90, 150, 210, 270 and 360 days after the beginning of the experiment corresponding to times 1, 2, 3, 4, 5 and 6 respectively. It was calculated the point of maximum growth for each evaluated parameter (plant height, shoot diameter, leaf area index, root, shoot, leaf and total dry weight) after 12 months of cultivation in pots. There were also determined the levels of fertilization corresponding to 90% of its maximum growth ranging from 70% to 112,25% of standard fertilization. Based in these levels it was calculated the range for the levels of leaf macronutrient. The obtained values were: 19,24 to 23,16 g..Kg-1 for nitrogen, 1,14 to 1,21g.Kg-1 for phosphorus; 17,29 to 19,02 g.Kg1 for potassium, 12,70 to 14,11 g.Kg-1 for calcium, 8,26 to 8,97g.Kg-1 magnesium,; and 1,49 to 1,77 g.Kg.-1 for sulfur.